Micropipette Aspiration‐Based Assessment of Single Channel Water Permeability. Issue 7 (11th May 2020) - Boytsov, Danila; Hannesschlaeger, Christof; Horner, Andreas; Siligan, Christine; Pohl, Peter
Abstract: Measurements of the unitary hydraulic conductivity of membrane channels, p f, may be hampered by difficulties in producing sufficient quantities of purified and reconstituted proteins. Low yield expression, the purely empiric choice of detergents, as well as protein aggregation and misfolding during reconstitution may result in an average of less than one reconstituted channel per large unilamellar vesicle. This limits their applicability for p f measurements, independent of whether light scattering or fluorescence quenching of encapsulated dyes is monitored. Here the micropipette aspiration technique is adopted because its superb sensitivity allows resolving p f values for one order of magnitude smaller protein densities in sphingomyelin and cholesterol rich giant unilamellar vesicles (GUVs). Protein density is derived from intensity fluctuations that fluorescently labeled channels in the aspirated GUV induce by diffusing through the diffraction limited spot. A perfusion system minimizes unstirred layers in the immediate membrane vicinity as demonstrated by the distribution of both encapsulated and extravesicular aqueous dyes. p f amounted to 2.4 ± 0.1 × 10 −13 cm³ s −1 for aquaporin‐1 that served as a test case. The new assay paves the way for directly monitoring the effect that interaction of aquaporins with other proteins or inhibitors may have on p f on a single sample. Abstract : The method works at low reconstitution densities of water conducting channels and is not limited by unstirred layers. It allows for simultaneous measurements of channel abundance by fluorescence correlation spectroscopy and visualization of inhibitor effects without changing the sample.